Fur Protein Regulates the Motility of Avian Pathogenic Escherichia coli AE17 Through Promoter Regions of the Flagella Key Genes flhD - Niu, Lulu; Cai, Weizhen; Cheng, Xi; Li, Zhe; Ruan, Jianming; Li, Fangguo; Qi, Kezong; Tu, Jian (Frontiers in Veterinary Science, 2022)
Avian pathogenic Escherichia coli (APEC) is an important pathogen causing several diseases in birds. It is responsible for local and systemic infections in poultry, seriously impeding the development of the poultry industry, and poses a potential risk to public health. The iron absorption regulatory protein Fur and the noncoding RNA, RyhB, that it negatively regulates are important factors in bacterial iron uptake, but the regulation of bacterial virulence genes varies greatly among different bacteria. We found that Fur is very important for the mobility of APEC. The expression of fur and RyhB is extensively regulated in APEC, and RyhB expression is also negatively regulated by Fur. A transcriptomic analysis showed that the genes significantly differentially regulated by Fur are related to cell movement, including cilium- or flagellum-dependent cell motility. To verify these results, we examined the effects of fur knockdown on cell movement by measuring the diameter of the bacteria colonies. Consistent with the RNA sequencing results, the mobility of AE17Δfur was significantly reduced compared with that of the wild type, and it had almost lost its ability to move. Using an electrophoretic mobility assay, we confirmed that the Fur protein directly binds to the promoter region of the key flagellum-related gene flhD, thereby affecting the assembly and synthesis of the APEC flagellum. This study extends our understanding of gene regulation in APEC.